The Key Success of Implementation of SIDILAN App in Improving the Quality of Public Services - Deby Febriyan Eprilianto; Dita Perwita Sari; Riyadi Riyadi; Dinar Ryzky Listyaputri; Refti Handini Listyani; Yuyun Eka Kartika Sari; Yeni Puspitasari; Nur Fadillah Sebti Sulistiana (Newinera Publisher, 2023)
The development of the Integrity Zone is based on Permenpan RB Number 10 of 2019 as an amendment to Permenpan RB Number 52 of 2014 concerning Guidelines for the Development of Integrity Zones Towards Corruption-Free Areas and Clean and Serving Bureaucratic Areas. The enactment of this regulation made Surabaya State University try to obtain the title of integrity zone by appointing the Faculty of Social Sciences and Law as a model faculty. In practice, the Social Sciences and Law faculty innovate digital-based public services through the Sidilan Application. This research aims to analyze the development and application of SIDILAN in improving the quality of public services. The research method used is descriptive with a qualitative approach. This research focuses on theories about the elements of successful e-Government development which include support, capacity and value. The research results show that these three indicators have supported the successful implementation and development of SIDILAN in improving the quality of public services in the Social Sciences and Law faculty. However, there are still no legal products from universities that use a legal basis. Apart from that, it is hoped that SIDILAN socialization can be carried out directly to increase understanding and minimize miscommunication regarding the services needed.